Job Attitude as a Factor on Employees Performance - Wendell Cabrera; Dennis Estacio (Yayasan Riset dan Pengembangan Intelektual, 2022)
An attitude is a psychological state of mind. It is the way a person thinks about situations, and it ultimately determines a person's behavior. In the workplace, employees can have either a positive or negative attitude about specific work tasks, products or services, co-workers or management, or the company as a whole. Positive attitudes among employees make workdays more enjoyable. Tasks are performed to a higher standard and without complaint. Current study is based on the effect of attitude on employee performance. This study includes the attitude related factors (behaviors of employees and leaders, job satisfaction, job commitment, motivation and training) to investigate their impact on employee performance. This study utilized descriptive method of research. An instrument was developed by the researcher with 8 statements to measure the perceived level of satisfaction, involvement, and performance and then distributed among the respondents with the five- point Likert scale. Result shows that all attitude related factors positively affect the employee performance. Motivation and job commitment has highly significant impact of performance of employees. As a result, organizations should value their experienced personnel and devise effective retention policy by giving competitive salary, experienced base pay and experienced based promotion. That will increase the overall performance of the organization. Keywords: Attitudes, performance, job satisfaction